Study of UHF near-field RFID antenna - Toh, Jun Hui. (2012)
The performance of a UHF near-field RFID segmented loop antenna is studied. In this report, the effects of integrating perfect electric conductor (PEC) to the segmented loop antenna will be investigated using the IE3D simulation platform then and validated through testing and measurement. Adding artificial magnetic conductor (AMC) did not yield desired improvements of performance from the PEC backed antenna. It only reduced the size of the antenna by a slight 10mm. However, the gains of the AMC backed antenna and PEC backed antenna are significantly better. The reading rate of the AMC/PEC backed antenna also improves by 20%.